1996
DOI: 10.1016/0306-4522(96)00254-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium currents in pyramidal CA1 neurons in vitro after kindling epileptogenesis in the hippocampus of the rat

Abstract: Calcium currents in pyramidal CA1 neurons in vitro after kindling epileptogenesis in the hippocampus of the rat Faas, G.C.; Vreugdenhil, M.; Wadman, W.J. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 49 publications
7
47
1
Order By: Relevance
“…Therefore, the primary utility of drugs effective in these screens would probably be against secondary generalization of seizures. However, it is clear from the studies described above and studies describing alterations in excitatory amino acid receptors (60)(61)(62)77) and other ion channels (64,(78)(79)(80) in focal tissue within the epileptic brain that many ion channels and receptors in these critical epileptogenic sites are fundamentally different from those in control tissue. Future efforts targeting these "epileptic" ion channels may have therapeutic benefit in controlling initiation of seizures rather than seizure spread.…”
Section: "Epileptic" Ion Channels: Implications For Drug Development mentioning
confidence: 94%
“…Therefore, the primary utility of drugs effective in these screens would probably be against secondary generalization of seizures. However, it is clear from the studies described above and studies describing alterations in excitatory amino acid receptors (60)(61)(62)77) and other ion channels (64,(78)(79)(80) in focal tissue within the epileptic brain that many ion channels and receptors in these critical epileptogenic sites are fundamentally different from those in control tissue. Future efforts targeting these "epileptic" ion channels may have therapeutic benefit in controlling initiation of seizures rather than seizure spread.…”
Section: "Epileptic" Ion Channels: Implications For Drug Development mentioning
confidence: 94%
“…Both increased and decreased activity of HVA Ca 2+ currents have been seen [Faas et al, 1996;Mody et al, 1990]. In several genetic models of epilepsy, the primary defect involved voltage-gated Ca 2+ channels, but the mechanism of epileptogenesis was not clear (Ryan, 1999].…”
Section: Membrane Propertiesmentioning
confidence: 99%
“…T channels are localized to the soma and dendrites of CA1 pyramidal neurons and, thus, well positioned to play an important role in neuronal excitability and synaptic plasticity [Magee et al, 1998]. Increased activity of T-type Ca 2+ currents was present in one model of absence epilepsy [Tsakiridou et al, 1995] and in brain slices from kindled animals [Faas et al, 1996]. The TTX model of epilepsy is one of the first to show the role of an altered Ca 2+ current in the developing brain.…”
Section: Membrane Propertiesmentioning
confidence: 99%
“…Epileptic seizure activity is associated with significant changes in calcium influx, intracellular calcium concentration, and calcium-dependent secondary mechanisms (Heinemann et al 1990;Faas et al 1996). Abraham and Huggett (1997) showed that in the CA1 region of the hippocampus, overstimulation transiently inhibits subsequent LTP induction through activation of voltage-gated calcium channels (VGCCs) and of NMDA receptors.…”
Section: Synaptic Plasticity In Kindled Ratsmentioning
confidence: 99%